ANALISIS AUSSPRACHEÜBUNGEN DALAM BUKU AJAR NETZWERK A1 - Tengku Fitrini Nurrachmah, - (2020)
In learning the German language, learner learn four language skills that cannot be separated from pronunciation (Aussprache). Aussprache is a part of the field of linguistics, namely phonology and also to speaking skills (Sprechfertigkeit). Pronunciation exercises (Ausspracheübungen) have an important role in the process of teaching the German language. Therefore, Ausspracheübungen was one of the most important components in the preparation of German teaching books. Netzwerk A1 is one of the German textbooks used in high school, in the German language courses and Colleges or Universities in Indonesia. The purpose of this study is to describe as well as to receive an overview of material that is available in the teaching book related the category of exercise type and theme of phonetic discussed and also the consistency of the material Aussprache with Gemeinsamer Europäischer Referenzrahmen (GER). The method used in this study is a descriptive analysis. The research data are analyzed based on the theories of Dieling and Hirschfeld (2000) about the category of exercise typology and the phonetic themes. The result showed that in the textbook Netzwerk A1-Kursbuch, which consists of 12 chapters, 10 of 15 phonetic themes according to Dieling and Hirschfeld are found. Based on the analysis, there ist also Dipthong, which is not part of the phonetic themes described by Dieling and Hirschfeld. In addition, the 6 exercise typologies are invented from 12 chapters, which consist of listening exercises and speaking exercises, and are divided into 38 exercises. The scope of the material in the textbook Netzwerk A1-Kursbuch is also suitable with the phonological competences that were found in the Gemeinsamer Europäischer Referenzrahmen (GER). Based on the analysis results, it is recommended that Ausspracheübungen in the course book Netzwerk A1 are used optimally both in class and by learners during independent learning.